MBOAT7 rs641738 (C>T) is associated with NAFLD progression in men and decreased ASCVD risk in elder Chinese population - Xu, Xiaoyi; Xu, Hangfei; Liu, Xiaohui; Zhang, Shuang; Cao, Zhenhuan; Qiu, Lixia; Du, Xiaofei; Liu, Yali; Wang, Gang; Zhang, Li; Zhang, Yang; Zhang, Jing (Frontiers in Endocrinology, 2023)
Background and aim: The MBOAT7 rs641738 (C>T) variant has demonstrated an association with non-alcoholic fatty liver disease (NAFLD) in both adult and pediatric patients, while few research has been conducted in elderly populations. Hence, a case control study was undertaken to assess their correlation in elderly residents in a Beijing community. Materials and methods: A total of 1287 participants were included. Medical history, abdominal ultrasound, and laboratory tests were recorded. Liver fat content and fibrosis stage was detected by Fibroscan. Genotyping of genomic DNA was performed using the 96.96 genotyping integrated fluidics circuit. Results: Of the recruited subjects, 638 subjects (56.60%) had NAFLD, and 398 subjects (35.28%) had atherosclerotic cardiovascular disease (ASCVD). T allele carriage was associated with higher ALT (p=0.005) and significant fibrosis in male NAFLD patients (P=0.005) compared to CC genotype. TT genotype was associated with reduced risk of metabolic syndrome (OR=0.589, 95%CI: 0.114~0.683, P=0.005) and type 2 diabetes (OR=0.804, 95%CI: 0.277~0.296, P=0.048) in NAFLD population when compared to the CC genotype. In addition, TT genotype also associated with reduced risk of ASCVD (OR=0.570, 95%CI:0.340~0.953, P=0.032) and less obesity (OR=0.545, 95%CI: 0.346~0.856, P=0.008) in the whole population. Conclusion: MBOAT7 rs641738 (C>T) variant was associated with fibrosis in male NAFLD. The variant also reduced risk of metabolic traits and type 2 diabetes in NAFLD and ASCVD risk in Chinese elders.